Transnational Practices Governing European Integration: Executive Autonomy and Neo-Corporatist Concertation in the Steel Sector. (13th April 2018) - KAISER, WOLFRAM
Abstract : The European Coal and Steel Community was marked by institutional innovations. They have masked strong continuities in administrative and business communities and their governance practices, however, which persisted after 1945. Based on fresh research in national and international organisation archives, this article explores the origins before, during and after the First World War of two key elements of these practices, their evolution over time and their influence on post-war Western European governance of the steel sector: the struggle for executive autonomy and close transnational industry cooperation. Both practices clashed in the ECSC, became amalgamated and had lasting impact on the present-day European Union and its democratic deficit.